KAJIAN KETERSEDIAAN KAYU BAKAR PADA PENGRAJIN GULA MERAH - Tjutju Nurhayati; Wesman Endom; Dadan Dadan (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
A survey pertaining to the topic as such has been conducted in three particular locations, where the sugar industries that consume fuel wood were situated, i.e. Jasinga (West Java), Gombong (East Java). and Karangasem (Bali). The inherent data were collected using the cluster-plot method to figure out the potential of available firewood in the community land. The main data covered the amount of organic foliage debris (i.e. twigs, small branches, etc.) which fall off the tree stands naturally, the potential volume of stands, and their regeneration rate to provide a reserve fuel wood which can be available whenever ii is needed. Meanwhile, the supplementary data were the firewood consumption, cooking stove efficiency, palm-sugar production, and palm-sugar yield and qualities, which in all were obtained through a trial observation in the field.